Interferon tipo I produzido por embriões in vitro na sinalização endócrina anterior ao período clássico de reconhecimento materno da gestação em bovinos - Bridi, Alessandra (2017)
Maternal recognition of pregnancy period in bovine is characterized when the concept secrets IFNT and signals its presence inside maternal uterus. IFNT main function is to maintain corpus luteum producing progesterone to establishment and maintain pregnancy. Conceptus derived-extracellular vesicles transport proteins responsible for signaling to the maternal organism in the pre-attachment period. Also, extracellular vesicles secreted by bovine endometrium stimulate conceptus trophectoderm IFNT production. Therefore, the aim this study was to evaluate whether in vitro fertilized (IVF) embryo-derived IFNT is capable to stimulate ISG15 expression in luteal cells culture, and also to identify if IFNT signal occurs in free protein form or via exosome. In experiment 1, it was evaluated if primary luteal cells culture responds to type I interferon treatment. ISG15 mRNA expression increased in luteal cells culture in a dose dependent manner reaching a plateau at 10ng/ml of interferon-alpha. In experiment 2, luteal cells culture treated with Day 12 conditioned medium by parthenogenetic activated embryos (paSOF), increased ISG15 mRNA expression when compared to paSOF from Days 7 and 9. Antiviral assay detected a greater bioactivity of type I interferon on Days 9 and 12 paSOF when compared to paSOF from Day 7. In experiment 3, IVF produced embryos were cultured until Days 7, 9 and 12 of development and followed by conditioned medium collection. IFNT2 mRNA expression was assessed on embryos from Days 7, 9 and 12 of development. On Day 9, IFNT2 mRNA expression was greater than Day 7, and no difference was observed on Day 12. ISG15 expression was evaluated on luteal cells culture treated with conditioned medium from IVF produced embryos on Days 7, 9 and 12 of development. Luteal cells culture treated with ivfSOF (SOF from embryos before of ultracentrifugation) and SN (SOF from embryos after of ultracentrifugation, depleted of extracellular vesicles) increased ISG15 mRNA expression when compared to EVs (pellet enriched with exosome obtained after ultracentrifugation of SOF from IVF embryos). Extracellular vesicles were labeled with PHK67 and their presence was observed inside the luteal cells. It is concluded, luteal cells culture respond to Type I interferon treatment present in the conditioned medium from IVF embryos as early as Day 7 of development, and this communication using interferons occurs in the free protein form.